Pengaruh Model Pembelajaran Inquiry terhadap Prestasi Belajar IPS Tema Kayanya Negeriku pada Siswa Kelas IV SDN Jatinegara Kaum 14 Jakarta Timur - Nabila Rizqika Kusumawardani; Ika Yatri (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
This research is a study on how to teach teachers to apply critical thinking students. The goal is to find out whether there is an Influence of the Inquiry Learning Model on Social Studies Learning Achievement with the theme of Kayanya Negeriku on grade IV students of SDN Jatinegara Kaum 14 East Jakarta. The method used is quasi-experimental design, the sample is class IV A 30 students and class B 30 students, so the population is 60 students. This study used the Posttest Only Control Group Design technique. This analysis test is in the form of a normality test (Liliefors test) and a homogeneity test (Fisher test). The final result of the t-test is thitung = 3.41 > ttabel = 2.0021, then H0 is rejected while H1 is accepted. With this, it has an implication that there is an Influence of inquiry learning models on social studies learning achievement with the theme of Kayanya Negeriku on grade IV students of SDN Jatinegara Kaum 14 East Jakarta. Penelitian ini merupakan penelitian mengenai cara mengajar guru untuk menerapkan siswa berpikir kritis. Tujuannya untuk mengetahui apakah terdapat Pengaruh Model Pembelajaran Inquiry Terhadap Prestasi Belajar IPS tema Kayanya Negeriku pada siswa kelas IV SDN Jatinegara Kaum 14 Jakarta Timur. Metode yang digunakan merupakan quasi experiment design, sampelnya yaitu kelas IV A 30 siswa dan kelas B 30 siswa, sehingga populasinya 60 siswa. Penelitian ini menggunakan teknik Posttest Only Control Group Design. Pengujian analisis ini berbentuk uji normalitas (uji Liliefors) dan uji homogenitas (uji Fisher). Hasil akhir uji-t yakni thitung = 3,41 > ttabel = 2,0021, maka H0 ditolak sementara H1 diterima. Dengan ini, memiliki implikasi bahwa ada Pengaruh Model Pembelajaran Inquiry Terhadap Prestasi Belajar IPS tema Kayanya Negeriku pada siswa kelas IV SDN Jatinegara Kaum 14 Jakarta Timur.